PENGARUH GAJI DAN INSENTIF TERHADAP KESEJAHTERAAN KARYAWAN DI PT WISMILAK INTI MAKMUR SURABAYA - Achmad Zaenal Arifin; Ida Aju Brahma Ratih (Jurnal Ilmiah Manajemen, Ekonomi dan Akuntansi, 2025)
Salaries and incentives are not merely factors that fulfill employees’ fundamental needs but also serve as motivators to enhance performance and well-being. This study aims to examine the significant influence of salary and incentives on employee well-being at PT Wismilak Inti Makmur, Surabaya. Employing a quantitative research method, this study utilized questionnaires as the data collection instrument, targeting a sample of 50 employees. The variables studied include Salary (X1), Incentives (X2), and Employee Well-being (Y). The findings reveal that the F-test yielded an F-value of 30.623, exceeding the F-table value of 2.81, with a significance level of 0.001 < 0.05. The t-test indicates that variable X1 has a t-value of 3.516 compared to a t-table value of 2.011, while variable X2 has a t-value of -7.521 compared to a t-table value of 2.011. This suggests that Incentives (X2) have a significant but negative influence on Employee Well-being (Y). The determination coefficient test shows an R² value of 0.566, implying that Salary (X1) and Incentives (X2) collectively explain 56.6% of the variance in Employee Well-being (Y). The study concludes that Salary (X1) has a positive influence on Employee Well-being.